Non-adherence to the World Health Organization's physical activity recommendations and associated factors among healthy adults in urban centers of Southwest Ethiopia. - Sabit Zenu; Endegena Abebe; Mohammed Reshad; Yohannes Dessie; Rukiya Debalke; Tsegaye Berkessa (Public Library of Science (PLoS), 2023)
Physical inactivity is a major risk-factor of non-communicable diseases. The World Health Organization has set physical activity recommendations for adults to reduce physical inactivity and its consequences. However, 1.4 billion adults are non-adherent to the recommendation worldwide. The prevalence of non-adherence to this recommendation and its predictors has not been assessed in urban Ethiopia. This study aimed to determine the prevalence of non-adherence to physical activity recommendations and identify its associated factors among healthy adults in urban centers of Southwest Ethiopia. A community-based cross-sectional study was employed from May to June 2021, involving 1191 adults in urban centers of Southwest Ethiopia. Data was collected using Global Physical Activity Questionnaire. Multivariable logistic regression was used to identify factors associated with non-adherence to physical activity recommendations using 95% confidence interval of adjusted odds ratio at P-value of < 0.05.Overall, 61.2% of participants were non-adherent to physical activity recommendations. Older age (AOR = 6.6; 95%CI (2.3-19)), female sex (AOR = 6.1; 95%CI (3.5-10.5)), lower educational status (AOR = 0.5; 95%CI (.28-0.93)), less community engagement (AOR = 2.7;95% CI (1.3-5.5)), lower level of happiness (AOR = 4.7; 95%CI (1.3-16.8)) and physical inactivity of family members (AOR = 2.5; 95%CI (1.4-4.3)) were associated with non-adherence. The prevalence of non-adherence to physical activity recommendations in the study area is high. Age, sex, educational status, community engagement, level of happiness and physical inactivity of family members were predictors of non-adherence to the recommendations. Interventions have to target females and older adults. Community participation and family based physical activity have to be advocated to avert the consequences of physical inactivity.